Evaluasi Konsumsi Makan dan Kepatuhan Konsumsi TTD terhadap Tingkat Kecukupan Zat Besi pada Remaja Putri di SMKN 1 Salatiga - Gelora Mangalik; Debora Brian Santika Wijayanti; Rifatolistia Tampubolon (Jurnal Epidemiologi Kesehatan Komunitas, 2023)
Background: Anemia is a nutritional problem, the 2018 Riskesdas data shows 48.9% of adolescent girls experience iron deficiency anemia. The government has made efforts to overcome the problem of anemia in adolescent girls through the provision of blood-supplementation tablets (TTD).Methods: This research used is descriptive with a quantitative approach, using a 2x24 hour instrument record, and the SQ-FFQ form. This study assesses the level of iron adequacy by looking at the data from the evaluation of food consumption which is expressed by the value of MAR (Mean Adequacy Ratio).Result: The results showed that respondents in consuming iron tablets were in the non-adherent category as much as 65%, the level of iron adequacy in the very poor category was 42.5%, the level of macronutrient intake in 42.5% of respondents experienced a severe level of deficit and the food intake of respondents was less varied.ConclusionÂ : The conclusion of this study is an evaluation of food consumption average has a weight deficit, the food consumed does not vary, iron intake is not sufficient according to the AKG, and is not obedient in consuming TTD.